Use of Species of Trichoderma sp. as an Alternative for Phytosanitary Control and Promotion of Plant Growth - Cordero, Alexander Pérez; Vergara, Donicer E. Montes; Mendoza, Yelitza Aguas (Journal of Ecohumanism, 2024)
Yield standards and diseases in horticultural crops are traditionally achieved with synthetic fungicide applications that increase production costs, however, this measure has shown negative effects. Therefore, the challenge of sustainable production imposes the transformation of conventional agricultural production systems to low-cost agroecological ones. Therefore, the objective was to determine the biocontrol capacity of native Trichoderma spp against Phytophthora cinnamomi and growth promotion in avocado and banana crops. Trichoderma spp were isolated by trap cultures in avocado crops and identified by molecular techniques. The antagonistic activity against P. cinnamomi and the growth promoting activity of Trichoderma was performed in vitro and in the greenhouse on avocado seedlings. Sequence analysis of the tef 1α gene of the 9 Trichoderma isolates identified them as T. viride and T. harzianum which showed inhibition against P. cinnamomi of 93.7% and 82.2%, respectively, while in the greenhouse the avocado plants showed no disease symptoms according to the severity scale (0). In vitro growth promotion showed that both species solubilized phosphate, produced siderophores and IAA and, in the greenhouse, increased all growth promotion variables in avocado and chili crops, compared to the control and the commercial product. In conclusion, T. viride and T. harzianum represent an important agroecological and biotechnological alternative that is low cost and environmentally friendly since they are native soil microorganisms.